Ruricius of Limoges, Caesarius of Arles, and Council of Agde 506 - Elena Litovchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The paper deals with the circumstances of holding the Council of Agde in 506 on the ground of the Council's resolutions, the epistolaries of Caesarius of Arles and Ruricius of Limoges. The study based on the context-historical analysis, which is especially useful for ego-documents, since it allows interpreting texts of personal sources taking into account specific cultural and historical conditions. As a result of the analysis, the author comes to the conclusion that the Council of Agde was convened on the initiative of the Visigothic king Alaric II, who, in a situation of the external threat aggravation, considered it as a means of consolidating the population of the former Roman provinces that were part of the barbarian state. The circumstances of the Council give an idea of the relationship between the secular and spiritual authorities in the period under study. The event was held under the chairmanship of the Bishop of Arles Caesarius. The Council was devoted mainly to issues of Church discipline. The decrees of this Council allow us to judge its significance and scale: representatives of almost all South Gallic cities (more than thirty representatives of Gallic clergy) took part in the Council; as a result of its work forty-seven canons were adopted. The correspondence of Caesarius and Ruricius about the Council of Agde acquaints us with the circumstances of its preparation and plans for the next meeting. It allows assessing the hierarchy of relationships within the Christian clergy, in a situation where one bishop (Ruricius) was subordinate to another (Caesarius) due to the seniority of his see, on the one hand, but, on the other hand, Ruricius had higher social status due to his origin. The latter fact, apparently, still played a significant role in communication between representatives of the clergy.